Anti-Inflammatory and Photoprotective Potential of Clitoria ternatea Extract in Mitigating UV-B-Induced IL-1β Elevation - Damayanti, Galih Sari; Kresnantio, Febryan Fadhil; Mahadewa, Narendra Lintang; Nursyafillah, Rizki Noval; Fany, Alfa Sofia (Journal of Biomedicine and Translational Research, 2026)
ABSTRACTBackground: Global climate change has escalated ultraviolet (UV) radiation exposure, contributing to skin aging and damage. Ultraviolet radiation, especially UV-B, is a known inducer of reactive oxygen species (ROS), which trigger inflammation and accelerate photoaging by increasing IL-1, IL-6, IL-8, and TNF-α levels. Clitoria ternatea, or butterfly pea, contains bioactive phytochemicals such as flavonoids and anthocyanins, known for their antioxidant and anti-inflammatory properties.Objective: This study aims to evaluate the effects of C. ternatea extract cream on serum IL-1β levels in UV-B-induced Wistar rats, exploring its potential in reducing photoaging and promoting skin health.Methods: True experimental study with post-test only control group design involving male Wistar rats for 30 days. The rats were divided into four groups: negative control with placebo (base cream) and treatment groups given 2.5%, 5%, and 10% C. ternatea extract cream, with UV-B induction applied for 30 minutes, three times per week. IL-1β were evaluated using ELISA Rat IL-1 kit.Results: Significant differences were observed between the negative control and extract-treated groups. The lowest IL-1β levels were recorded in the 2.5% and 5% extract groups (p<0.001), indicating a strong anti-inflammatory effect. The findings suggest that C. ternatea extract cream, especially at 2.5% and 5% concentrations, effectively reduces IL-1β levels in UV-B-induced Wistar rats. The bioactive compounds in C. ternatea, such as anthocyanins and flavonoids, may inhibit ROS production and inflammation pathways. This study demonstrates that C. ternatea extract cream can reduce IL-1β levels, potentially mitigating UV-induced skin damage.Conclusion: The C. ternatea extract’s anti-inflammatory properties make it a promising candidate for skincare products aimed at reducing photoaging. Further studies are recommended to explore the effects of higher concentrations and long-term applications in clinical settings. Keywords: Clitoria ternatea extract, IL-1β modulation, antiphotoaging, photoprotective agents, herbal skincare.